2003
DOI: 10.1177/031289620302800202
|View full text |Cite
|
Sign up to set email alerts
|

Momentum in Australian Stock Returns

Abstract: Medium-term momentum, or the tendency of investment strategies based on buying past winning stocks while selling past losing stocks to maintain above normal performance over a period, has been a well-documented feature of stock returns in the US. We investigate the performance of momentum investment strategies in portfolios of Australian stocks and examine some of the common explanations and empirical features of momentum. The paper establishes the presence of a strong medium-term momentum effect, which cannot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
81
3
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 20 publications
7
81
3
1
Order By: Relevance
“…Grundy and Martin (2001) further state that the momentum return is not explained by either industry effect or cross-sectional dispersion in mean returns. Hurn and Pavlov (2003) add that no single factor can explain momentum return. Du and Denning (2005) suggest that momentum return is due to common factors, rather than industry-specific risk.…”
Section: Industrial Momentummentioning
confidence: 99%
“…Grundy and Martin (2001) further state that the momentum return is not explained by either industry effect or cross-sectional dispersion in mean returns. Hurn and Pavlov (2003) add that no single factor can explain momentum return. Du and Denning (2005) suggest that momentum return is due to common factors, rather than industry-specific risk.…”
Section: Industrial Momentummentioning
confidence: 99%
“…Rouwenhorst (1998) found evidence supporting the existence of momentum strategies in 12 European countries during the period 1980-1995, additional evidence has been obtained from the Australian market (Hurn & Pavlov, 2003). In addition Griffin et al (2003) measured momentum profits internationally, by taking samples from all the continents, and the results showed that momentum profits are significant in all regions except Asia with emerging market showing weaker profits compared to developed ones.…”
Section: Momentummentioning
confidence: 82%
“…Similarly in Australia, Hurn and Pavlov (2003) identified a strong medium-term momentum effect in Australian stock returns. This was confirmed by Demir et al (2004) who found there was a greater magnitude of momentum returns from Australian equities in comparison to momentum returns from other share markets.…”
Section: Introductionmentioning
confidence: 92%